Risk patterns, structural characteristics, and organizational configurations1. (July 2017) - Renzi, Antonio; Sancetta, Giuseppe; Orlando, Beatrice
Abstract: A firm's structural characteristics are predictive of its risk pattern and attitude toward managing change over time. Idiosyncratic risk has its roots in the firm's structure. This affects the firm's volatility compared with the average volatility in the sector. Such characteristics and risk patterns affect the firm's capability to manage change and capture the value from change.